2019
DOI: 10.1055/s-0039-1691807
|View full text |Cite
|
Sign up to set email alerts
|

Is Lactoferrin More Effective in Reducing Late-Onset Sepsis in Preterm Neonates Fed Formula Than in Those Receiving Mother's Own Milk? Secondary Analyses of Two Multicenter Randomized Controlled Trials

Abstract: Background Lactoferrin is the major antimicrobial protein in human milk. In our randomized controlled trial (RCT) of bovine lactoferrin (BLF) supplementation in preterm neonates, BLF reduced late-onset sepsis (LOS). Mother's own milk (MM) contains higher concentrations of lactoferrin than donor milk or formula, but whether BLF is more effective in infants who receive formula or donor milk is uncertain. Aim To evaluate the incidence of LOS in preterm infants fed MM and in those fed formula and/or do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Available secondary analyses of the small subset of exclusively formula-fed infants raise the question of whether these patients may benefit from lactoferrin supplementation, but the current data are insufficient to address this with certainty [17, 18]. Furthermore, we found that human lactoferrin has greater activity against common neonatal pathogens in vitro, with an early trial of recombinant human lactoferrin (talactoferrin) demonstrating no safety concerns and a trend towards lower sepsis rates in the treatment arm.…”
Section: Discussionmentioning
confidence: 88%
“…Available secondary analyses of the small subset of exclusively formula-fed infants raise the question of whether these patients may benefit from lactoferrin supplementation, but the current data are insufficient to address this with certainty [17, 18]. Furthermore, we found that human lactoferrin has greater activity against common neonatal pathogens in vitro, with an early trial of recombinant human lactoferrin (talactoferrin) demonstrating no safety concerns and a trend towards lower sepsis rates in the treatment arm.…”
Section: Discussionmentioning
confidence: 88%
“…An interim analysis of the primary composite endpoint and of survival to discharge using the Haybittle-Peto [28] approach in the first 250 infants enrolled in the study in Canada. The procedure involves evaluating the test statistic calculated under the null hypothesis against a boundary of 3 standard deviations (equivalent to χ 2 = 9, with a p-value of 0.0027.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta-analysis of the effect of bLF on late onset sepsis in 1891 preterm infants who were not fed exclusively mother's own milk in two RCTs of bLF supplementation [25,27,28], a relative risk of late onset sepsis to be reduced to 0.82 (95% 0.71-0.96; P = 0.01), with moderate heterogeneity (I 2 = 0.64) and asymmetric funnel plot, consistent with small study effects, or true differences between trials in effectiveness or underlying patient risk [29].…”
Section: Rationale For Continuing Lift_canadamentioning
confidence: 99%
“…The ELFIN [15] study in the UK used a dose of 150 mg/kg of bovine LF, with no significant protective effect against LOS, suggesting that probably a higher dose is needed on top of the amount that neonates are already receiving from MOM. A recent study by Manzoni et al [27] evaluated the effect of bovine LF supplementation from 2 previous clinical trials and compared the effect among infants receiving only formula and mixed feeds. This study suggested that bovine LF supplementation may have a benefit among infants who do not receive MOM, and that probably there is no advantage of giving more LF to infants who are already receiving good quantities of MOM.…”
Section: Discussionmentioning
confidence: 99%